Responsibility of the Board of Directors for Tax Billings of the Bankrupt Company (A Case Study of PT United Coal Indonesia's Tax Debt Claims Which Have Been Declared Bankrupt by the Commercial Court) - Fadjrin Wira Perdana; Joko Setiyono; Wahyudi Siswanto; Sri Kartini; Irwan Irwan (Budapest International Research and Critics University, 2021)
Based on the KUP Law, companies that have been declared bankrupt by the Commercial Court are still burdened with tax debt because the Commercial Court's Bankruptcy Decision only stops the company's wheels but does not stop the tax debt. On the other hand, related to tax debt, based on the Limited Liability Company Law, it is the responsibility of the company's Board of Directors, so that companies that have been declared bankrupt still have to pay tax bills as happened to PT. United Coal Indonesia (PT. UCI).